The endless modernity of Iraqi art represents a parallel to it in the productions of art education students (Al-Academy, 2025)
The research entitled (Representations of endless, reticular modernity in contemporary Iraqi art and its role in the productions of art education students) consisted of four chapters. The first chapter defined the methodological framework of the research, which began with the problem and ended with the following question: What are the representations of endless, reticular modernity in contemporary Iraqi art, and what is its role in the products of education students? Artistic? The first chapter also included the goal of the research, its importance, and the need for it. The second chapter included two sections. The first section dealt with the infinite networked modernity, while the second section dealt with: contemporary Iraqi art (representations after post-modernism), while the third section devoted the research procedures, which included The research community and its sample. The researcher adopted the (descriptive) research method as it is the closest approach to achieving the research goal. The research included a population of (10) artistic products. The researcher chose a purposive sample of (3) artistic products. The researcher designed his research tool based on the indicators of the theoretical framework . And previous studies, validity and reliability were extracted, and the chapter concluded with an analysis of the samples, in light of the resultsThe research resulted in a number of recommendations and proposals.